WHATSAPP BUSINESS WORKSHOP AS A DIGITAL MARKETING PRACTICE TOOL FOR MARKETING STUDENTS OF SMK IQRO PASAR KEMIS - Lukman Azhari; Syepry Maulana Husain; Ri Sabti Septarini (Community Services and Social Work Bulletin, 2025)
Amid limited digital-marketing practice in vocational curricula, 80 grade-XI marketing students of SMK Iqro, Pasar Kemis, completed a four-day WhatsApp Business (WAB) workshop. Grounded in experiential-learning theory, the intervention blended classroom tutorials, hands-on catalogue creation, and field mentoring for five nearby MSMEs. Pre-test/post-test results showed a significant knowledge leap (51.9 ± 9.7 to 87.2 ± 6.4; Cohen’s d = 3.3, p < 0.001). Ninety-five percent of students produced full WAB catalogues and 89 % activated automated replies. Partner MSMEs recorded a 2.1-fold rise in customer inquiries after implementing student-designed broadcast campaigns. The study confirms that a brief, low-cost workshop can simultaneously elevate student competencies and deliver tangible benefits to local enterprises.